THE INFLUENCE OF JOB SKILL AND SERVICESCAPE ON CONSUMER SATISFACTION AT VAL BARBERSHOP IN SOLOK CITY - Herda Ofdiska; Rasidah Nasrah; Seflidiana Roza (SEAN Institute, 2023)
To support the success of a business and customer satisfaction, Val Barbershop and other developing barbershops need human resources or employees who already have skills in their field. As well as servicescape which is a physical design that can support placement and segmentation strategies. Thus, this research aims to determine the influence of job skills and servicescape on consumer satisfaction. This type of research is correlative research with a quantitative approach. The population of this study are consumers who visit and use services at Val Barbershop in Solok City, with an average of 10 visitors/day or 300 people/month. The sampling technique used in this research is incidental sampling. The data used is primary data obtained from questionnaires distributed to 100 respondents who are consumers who visit and use services at Val Barbershop in Solok City. Partially, the research results show that job skills influence consumer satisfaction and servicescape influences consumer satisfaction. Meanwhile, job skills and servicescape simultaneously influence consumer satisfaction. And the coefficient of determination test shows the results that consumer satisfaction is influenced by job skills and servicescape variables as much as 28.3%, and the remaining 71.7% is influenced by other variables outside the variables of this research.